(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
The study assessed people’s willingness to accept repentant Boko Haram and the role of Government and Non-Governmental organizations toward public risk-free coexistence campaigns. Primary and secondary roots of data were used for this study. First, a structured questionnaire was used to source data from 382 sampled respondents. The results revealed that most respondents were affected by Boko haram, 74%, while 26% were not. Furthermore, the study also showed that most respondents are not ready to accept Boko Haram Repentance, with 79% because they killed their relatives, burned their social environments, caused hardship, and migrated. Also, they fear that when the Government fails to fulfil their promise, they can rejoin the group because they are not to be trusted. At the same time, with few people, 21% are ready to accept the Boko Haram repentance because they believe peace will be restored. Some of the reasons are some were forced to join the group, some were their relatives, and lastly, some were brainwashed. Finally, the following recommendations were proffered. Firstly Government and NGOs should increase their efforts to enlighten the people to accept Boko Haram because, based on the findings, enlightenment camping is not enough. Secondly, the Government should ensure they fulfilled their promise to Boko Haram repentance after they were integrated because if they fail, they can rejoin the group again.